“We are much more than that” Upgrading consciousness through Yoga praxis - Juan Camilo Roman Estrada 1978- (2019)
Þessi ritgerð er lokaritgerð til MA prófs í trúarbragðafræði við Háskóla Íslands. Hún byggist á kenningarlegri rannsókn á möguleikum þess að þróa meðvitundina með iðkun nútímajóga, einkum í tengslum við sálfræðikenningar Jung. Nútímajóga, ásamt sálfræði Carl Gustav Jung (1875-1961) virðast eiga það sammerkt að líta svo á að þróun mannsins felist í að uppfæra (e. upgrading) mannlega meðvitund (e. consciousness) í flóknara form sem felur í sér annars konar vitund. Byggt er á því að þróun slíkrar heilstæðrar meðvitundar geri mannkyninu betur kleift að aðlaga sig að raunveruleikanum og skapa sér heilbrigðan og heilsteyptan lífsstíl. Sem viðbót og stuðning við fræðilegu nálgunina gerði ég eigindlega rannsókn í því skyni að kanna beina reynslu af jógaiðkun í Reykjavík nútímans. Ég nota rannsóknina til þess að bera saman upplifun þátttakenda við fræðilegar kenningar um efnið. The present paper is my master thesis for an MA degree in Religious Studies at the University of Iceland. It is based on a theoretical exploration about the possible evolution of consciousness through the practice of modern yoga with the support of Jungian psychology. Modern yoga, along with the depth psychology of Carl Gustav Jung (1875-1961) seem to agree that human evolution might consists in upgrading the human consciousness into a more complex model of operation and functionality, that somehow transcends and integrates multiple forms of awareness (including rationality). It is presumed that the development of this integrative type of consciousness will enable a human being to adapt to reality in more harmonious ways, becoming able to create a wholesome and integral lifestyle. Complementing the theoretical approach, I conducted a qualitative research in order to explore some direct experiences of yoga practice in present time Reykjavík (Iceland) and to find correlations with the theoretical understanding previously developed.